Konstanzer Seminar on Monetary Theory and Monetary Policy - Roland Schmidt (Kredit und Kapital, 1988)
Konstanzer Seminar on Monetary Theory and Monetary Policy Das diesjährige 19. Konstanzer Seminar on Monetary Theory and Monetary Policy beschäftigte sich schwerpunktmäßig mit Fragen der Geldmengensteuerung, Wechselkurserklärung und der privaten Alterssicherung. Der Bericht faßte die acht vorgetragenen Studien und die Diskussionen zusammen. – – Konstanzer Seminar on Monetary Theory and Monetary Policy The 19. Konstanz Seminar on Monetary Theory and Monetary Policy dealed with the control of the money supply, exchange rate explanations and the scope for deregulation of the old-age pension scheme. The report summarized the eight presented studies and the discussions.
Keywords: 330